Rethinking Conceptual Parameters of Choreography (in Social Spaces) : Actualization of Intensities in Discursive Fields - Monni, Kirsi (MDPI, 2024)
This article aims to take part in the ongoing discussion on the social and political potentialities as well as the conceptual premises of choreography and to contribute to the discussion about world relations in the choreographed movement. The much-used definition of Western choreography is “organized movement in space and time”. Although this definition always applies, it does not specify the world relations and worldmaking capacities of the choreographed movement. The main focus of this article is an ontological rethinking of the basic concepts of choreography: movement, space, time and organization, with the addition of kinaesthetic fields, kinaesthetic and spatial intelligence, virtual and actual realms, striated and smooth spaces (Deleuze and Guattari) and different conceptions of time. By analyzing these concepts, the aim is to provide a view of ontologically elementary units in choreography (such as a change in space, the difference over time and space, and passage to shared actuality), with a wider understanding of the inherent social relationality in choreographed movement. After discussing these topics, a few social choreography events and protests are described to represent different choreographic aims and organizational modes arising from each specific situation. The article concludes by proposing that choreography could be seen as organizing movement in space and time but also as a choreographic actualization of intensities in different discursive fields.
Keywords: tanssi; koreografia; tila; filosofia; tanssiteokset; estetiikka; ruumiillisuus; taiteellinen työ